What is international relations? - JORGENSEN, KNUD ERIK (Bristol University Press, 2021)
As International Relations enters its second century as an academic discipline, leading expert Knud Erik Jørgensen provides a provocative assessment of its past, present and future. The result is a concise and challenging appraisal of the discipline, one which both celebrates its value and maps possible future directions.